Preface by Editor-in-Chief - Baranauskienė, Ingrida (Social Welfare: Interdisciplinary Approach, 2020)
Dear authors, members of the editorial board, and readers of the scientific interdisciplinary journal Social Welfare: Interdisciplinary Approach. We present to you one more issue of the journal. As in previous issues, in the present issue, an interdisciplinary approach to social welfare in a national and intercultural context is important to us. In this issue, we present to your attention the works of scientists from three countries in one way or another related to social welfare, the concept of which is constructed and presented in three chapters: Social Challenges, The Development of Professional Competences and Disability Studies. Going deeper into the presented scientific works, it can be seen that in many of them we can name social justice as the main idea. This scientific concept and the starting point of the formation of the concept of life has reached us from ancient times. All of us know Plato, Socrates’ disciple, and his ontological concept of justice related to a virtue of the soul. Justice for Plato is one of the major virtues that encompasses both state governance and human life in general. It can be argued that he saw the benefits of justice in the life of the state and the individual, including the idea that justice unites society (Plato, 2000[1]). Aristotle gives justice the meaning of redistribution and sharing. On the other hand, although Aristotle’s justice is restricted to Greek citizens, in any case, the idea of sharing, redistributing, offsetting was spread thanks to Aristotle (Aristotle, 1990[2]). Thomas Aquinas not only linked the Christian tradition to the teaching of Aristotle, but also further developed the idea of justice and emphasized the importance of transposing the idea into law (Aquinas, 2015[3]). Immanuel Kant developed a moral theory which, in the context of our days, is, in my view, an important duty as the strongest pillar of morality (Kant, 1987[4]). Without going into polemic about how much Immanuel Kant’s philosophy influenced John Rawls’ theory of social justice, I will quote the principles of justice defined by him: “a) each person is to have an equal right to the most extensive scheme of equal basic liberties compatible with a similar scheme of liberties for others; and in this scheme the equal political liberties, and only those liberties, are to be guaranteed their fair value. b) Social and economic inequalities are to be arranged so that they are both: (a) to the greatest benefit of the least advantaged, consistent with the just savings principle, and (b) attached to offices and positions open to all under conditions of fair equality of opportunity” (Rawls, 2002, p. 61[5]). It can be said that Rawls’ idea that we will not achieve social welfare in the state until justice, including social justice, is ensured, has laid the foundations for a modern understanding of social justice. The dialectic of the concept of justice is also reflected in the works of our authors as the emphasis on justice as a value (Arūnas Acus, Liutauras Kraniauskas; Ilona Dobrovolskytė), the disclosure of the meaning of sharing (Jurgita Lenkauskaitė; Olga Kuprieieva, Tetiana Traverse, Liudmyla Serdiuk, Olena Chykhantsova, Oleksandr Shamych), the construct of the concept of law (Daiva Malinauskienė, Aistė Igorytė; Ingrida Baranauskienė, Alla Kovalenko, Inna Leonova), the understanding of a theory of civic morality, a duty that is a pillar of morality (Svitlana Kravchuk; Elena Kuftyak; Asta Volbikienė, Remigijus Bubnys; Simas Garbenis, Renata Geležinienė, Greta Šiaučiulytė). And it does not matter at all whether this is analyzed in the context of social challenges, disability studies or professional competences. It can be stated that the idea of social justice is the driving force behind the scientific works of this journal. Wishing everyone to stay healthy, both physically and spiritually, I place social justice as a fundamental value in these turbulent times of a global pandemic. But life does not stand still, so we look forward to your new research works. There will be no us without you.